Sonic hedgehog signalling mediates astrocyte crosstalk with neurons to confer neuroprotection - Ugbode, Christopher I. (J Neurochem, 2017)
Sonic hedgehog (SHH) is a glycoprotein associated with development that is also expressed in the adult CNS and released after brain injury. Since the SHH receptors patched homolog‐1 and Smoothened are highly expressed on astrocytes, we hypothesized that SHH regulates astrocyte function. Primary mouse cortical astrocytes derived from embryonic Swiss mouse cortices, were treated with two chemically distinct agonists of the SHH pathway, which caused astrocytes to elongate and proliferate. These changes are accompanied by decreases in the major astrocyte glutamate transporter‐1 and the astrocyte intermediate filament protein glial fibrillary acidic protein. Multisite electrophysiological recordings revealed that the SHH agonist, smoothened agonist suppressed neuronal firing in astrocyte‐neuron co‐cultures and this was abolished by the astrocyte metabolic inhibitor ethylfluoroacetate, revealing that SHH stimulation of metabolically active astrocytes influences neuronal firing. Using three‐dimensional co‐culture, MAP2 western blotting and immunohistochemistry, we show that SHH‐stimulated astrocytes protect neurons from kainate‐induced cell death. Altogether the results show that SHH regulation of astrocyte function represents an endogenous neuroprotective mechanism. [Image: see text]